2010
DOI: 10.1007/978-3-642-12029-9_15
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Consistency Checking of Dynamic Constraints

Abstract: Software design models are routinely adapted to domains, companies, and applications. This requires customizable consistency checkers that allow engineers to dynamically adapt model constraints. To benefit from quick design feedback, such consistency checkers should evaluate the consistency of such changeable constraints incrementally with design changes. This paper presents such a freely customizable, incremental consistency checker. We demonstrate that constraints can be defined and redefined at will. And we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…In [12] and [9], we have shown that the Model/Analyzer is capable of validating constraints instantly, even for large industrial models of over 100,000 model elements. Moreover, it was demonstrated that adding constraints (or removing them) is handled efficiently.…”
Section: Preliminary Performance Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [12] and [9], we have shown that the Model/Analyzer is capable of validating constraints instantly, even for large industrial models of over 100,000 model elements. Moreover, it was demonstrated that adding constraints (or removing them) is handled efficiently.…”
Section: Preliminary Performance Resultsmentioning
confidence: 99%
“…Consistency Checking After updating the set of constraints imposed by the metamodel, standard consistency checkings mechanisms (e.g., [8,9]) can be used to detect inconsistencies. While the typical scenario is that an unchanged model becomes inconsistent after metamodel evolution, it is also possible that a previously inconsistent model becomes consistent without any adaptations.…”
Section: Constraint Managementmentioning
confidence: 99%
“…In [6], [7] also transformation approach is followed. Groher et al [8] makes use of description logic in order to find discrepancies between state chart and sequence diagrams. Campbell et al [9] explored a model named SPIN for consistency checking in UML.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, a constraint is violated if its corresponding view is not empty. Other techniques follow a different approach aimed at incrementally checking the OCL constraints [5,6,7]. That is, assuming that no OCL constraint is violated for the current data, they determine which OCL constraints should be checked, and for which data, after some update is applied to the information system.…”
Section: Fig 2 Ocl Constraints For the Simplified Uml Class Diagrammentioning
confidence: 99%